Appearing the motivation of culture research through developing the Minangkabau culture subject based portfolio model - Muhiddinur Kamal; Z. Mawardi Effendi; Firman Firman; Taufina Taufik (International Conferences on Educational, Social Sciences and Technology)
The goals of this research are 1). To Develop the learning of BAM in portofolio based model in Islamic Junior High School, 2). To test the validity, practicality and the efectifity of the developed learning. This research was done by using research and devepment (R&D) research, by using Mc Kenny development which was adopted by Plom. There were three phases to design this research: prelimanary research, design and evaluation. To apply the development of learning in the classroom , the researcher designed the teacher’s book, the student’s book, the guide book and also the validity testing, practicality and the efectivity of the book which is refering to the designed of learning. In the process of the research, the qualitative data was collected throug observation, interview and field note. Meanwhile, in quantitative data was collected throug test and question. Then, the research did the data analisis and the final learning development of Minangkabau Culture Lesson (BAM). The result of the research were: a). The development of the learning of BAM in portofolio model which was developed in the form of guide book model, and learning device the teacher’s book and the student’s book. b). The user of the learning development of Minangkabau Culture Lesson (BAM) in portofolio based emperically can in crease the student’s motivation in learning.